High-frequency brain activity and muscle artifacts in MEG/EEG: A review and recommendations - Muthukumaraswamy, Suresh (Frontiers in Human Neuroscience, 2013)
In recent years high-frequency brain activity in the gamma-frequency band (30 to 80 Hz) and above has become the focus of a growing body of work in MEG/EEG research. Unfortunately, high-frequency neural activity overlaps entirely with the spectral bandwidth of muscle activity (~20-300 Hz). It is becoming appreciated that artifacts of muscle activity may contaminate a number of non-invasive reports of high frequency activity. In this review, the spectral, spatial and temporal characteristics of muscle artifacts are compared with those described (so far) for high-frequency neural activity. In addition, several of the techniques that are being developed to help suppress muscle artifacts in MEG/EEG are reviewed. Suggestions are made for the collection, analysis and presentation of experimental data with the aim of reducing the number of publications in the future that may contain muscle artifacts.